’Die enorme hoeveelheid informatie...’ De mateloze reconstructie van een oorlogsmisdaad - Honig, J.W. (BMGN - Low Countries Historical Review, 2003)
’Information overload... ’ The endless reconstruction of a war crime, J. W. Honig The NIOD-report on Srebrenica chose to ignore the pressing nature of the questions that the massacre had given rise to in the Netherlands and that led to launch of the investigation in 1996. The political and social relevance of the investigation was compromised by the excessive time it took to deliver the report (five-and-a-half years) and its bulk (6600 pages) whose accessibility was further marred by the chronological structure and narrative approach. But even if one accepts the rapporteurs’ stated intent that they merely wanted to produce ’an academic monograph’ then the work has serious shortcomings. A consideration of the explanation of the massacre reveals a careless use of primary sources, a continual failure to distinguish clearly the wood for the trees and conclusions that are not properly supported by often confusing and contradictory arguments. Most critically, though the report aims to provide ’analytical explanatory judgements’, these often fall short. The final conclusions regarding the key question of the main motives behind the massacre therefore not only fail to convince, but the way in which they are arrived at casts serious doubts as to the academic quality and validity of the report as a whole. This review is part of the discussion forum ’Srebrenica, een "veilig" gebied’ (J. C. H. Blom, B. G J. de Graaff, D. C. L. Schoonoord).